Auditor in fabula - la Bible dans son contexte oral : Le cas du livre de Ruth - Béré, Paul (Old Testament essays, 2006)
This article explores the idea that the oral finality of the biblical text must have imposed some formal constraint upon the written text. The authorial audience is not only made up of readers but in great part of listeners. Therefore, a methodological distinction should be made between "reader" and "hearer". As a matter of fact, an aural reception of a biblical narrative obeys its own principles. The study first presents some of them, and then uses the book of Ruth as an illustrative case. And indeed, some aspects of the narrative, previously unnoticed to "readers", come to the fore.